Decrease in rate of multiple sclerosis-related hospitalizations in Portugal - Pereira, Marta (F1000Research, 2016)
We sought to investigate the rate of multiple sclerosis (MS)-related hospitalizations in Portugal and assess whether there have been temporal changes as described in other countries. Using data from the Portuguese National Discharge Registry, we observed that between 2008 and 2013 the rate of MS-related hospitalizations decreased by 44%, from 15.9/100 person-years (95% confidence interval (CI: 14.9-16.9) in 2008 to 8.9/100 person-years (95% CI: 8.2-9.6) in 2013. The change in hospitalization rates is in accordance with what has been observed in other countries, and coincides with the release of new therapies for MS in Portugal.